Improvements in the Thrombin Generation Test - Ollendorff, Preben (Thrombosis and Haemostasis, 1960)
The influence of glass contact on the thrombin generation test was demonstrated and a modified method described.Nearly all prothrombin had been converted to thrombin before the thrombin concentration reached its maximum.